Development of Life-Saving Buoy Ring With Remote Control System - Ada, Welem; Zulaikah, Siti; Yusyarif, Idham Sri; Saputra, Andi Muh Akbar; Taufik, Ashabul (PT. Hafasy Dwi Nawasena, 2024)
This research focuses on the development of life-saving life saving rings equipped with remote control systems, with the aim of improving efficiency and effectiveness in emergency rescue in waters. The urgency of this research lies in the creation of a remotely operable buoy, thereby reducing reliance on physical strength and human accuracy during the rescue process. This research follows the ADDIE development model, which includes five phases: analysis, design, development, implementation, and evaluation. The design of the buoy and the accompanying remote control system are designed with user-friendliness and operational effectiveness in mind. The system is then tested by maritime professionals to assess its practicality and functionality. The test results showed a positive response from users, who gave a high assessment of the design and performance of the buoy. However, there are suggestions to increase the battery life of the remote control to support longer operations. Overall, the development of this life-saving buoy with a remote control system has made a significant contribution to maritime safety. By offering a more reliable and efficient solution, it can improve the quality of rescue operations, reduce the risk of accidents, and improve response in emergency situations in waters.